Firm lifecycles and external restructuring - Ari Hyytinen; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2011)
This paper studies how firms contribute to the productivity growth of an industry over their lifecycle. We present a decomposition method that allows us to condition the components of productivity growth on the age of production units. We find evidence for a prolonged positive exit effect that mirrors market selection during the early stages of firms'; lifecycle. This effect is tightly related to the negative initial productivity effect of entry. We also find some evidence that productivity-enhancing reallocation of resources between firms is concentrated on the middle aged firms.
Keywords: O12; O14; O47; 330; Productivity; decomposition; lifecycle; entry; exit; Produktivität; Lebenszyklus; Markteintritt; Marktaustritt; Dekompositionsverfahren; Finnland